The Bahamas : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper makes the case for a rules-based fiscal framework for The Bahamas and discusses its design, calibration, and implementation. The IMF staff recommends adopting a headline deficit ceiling and a cap on current expenditure growth, both calibrated to guide debt toward a suitable medium-term anchor while allowing room for stabilization. A headline deficit target is simpler to communicate and monitor than a structural balance rule. Such a framework would allow expanding capital spending, up to the limit provided by the deficit ceiling, in the event of improvements in revenue performance. Moreover, in line with best practices, the framework should be anchored around a pre-defined medium-term debt target that will guide the calibration of proposed operation rules.